Cognitive challenge as a probe to expose sex- and age-related differences during static contractions - Pereira, Hugo M.; Hunter, Sandra K. (Frontiers in Physiology, 2023)
Despite activities of daily living being frequently performed simultaneously with a cognitive task, motor function is often investigated in isolation, which can hinder the applicability of findings. This brief review presents evidence that 1) performing a cognitive challenge simultaneously with a motor task can negatively impact force steadiness and fatigability of limb muscles during a static contraction, 2) the negative impact on old adults (>65 years old), particularly older women is greater than young when a cognitive challenge is simultaneously performed with a static motor task, 3) age-related mechanisms potentially explain impairments in motor performance in the presence of a cognitive challenge, and 4) the mechanisms for the age-related decrements in motor performance can be distinct between men and women. These observations are highly relevant to the older adults, given the increased risk of accidents and injury when a motor task is performed with a high cognitive-demand task, especially in light of the expanding reliance on an aging workforce.